2015
DOI: 10.3390/ijms161126048
|View full text |Cite
|
Sign up to set email alerts
|

Brazilein Suppresses Inflammation through Inactivation of IRAK4-NF-κB Pathway in LPS-Induced Raw264.7 Macrophage Cells

Abstract: The medicinal herbal plant has been commonly used for prevention and intervention of disease and health promotions worldwide. Brazilein is a bioactive compound extracted from Caesalpinia sappan Linn. Several studies have showed that brazilein exhibited the immune suppressive effect and anti-oxidative function. However, the molecular targets of brazilein for inflammation prevention have remained elusive. Here, we investigated the mechanism underlying the inhibitory effect of brazilein on LPS-induced inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 39 publications
0
23
0
2
Order By: Relevance
“…The GSK-3β inhibitor LiCl effectively inhibited inflammatory cytokines by the increasing GSK-3β (Ser9) phosphorylation and GSK-3β inactivation. 32,34 Compared to LiCl treatment, K313 better inhibited NO, IL-6, and TNF-α secretion. Furthermore, K313 and LiCl had a synergistic effect on inhibiting NO, IL-6, and TNF-α secretion ( Figure 6A-C).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The GSK-3β inhibitor LiCl effectively inhibited inflammatory cytokines by the increasing GSK-3β (Ser9) phosphorylation and GSK-3β inactivation. 32,34 Compared to LiCl treatment, K313 better inhibited NO, IL-6, and TNF-α secretion. Furthermore, K313 and LiCl had a synergistic effect on inhibiting NO, IL-6, and TNF-α secretion ( Figure 6A-C).…”
Section: Discussionmentioning
confidence: 98%
“…LPS‐induction increased the constitutive activity of GSK‐3β to induce NO, TNF‐α, and IL‐6 secretion in RAW264.7 macrophages, but K313 had anti‐inflammatory effects by increasing the phosphorylated GSK‐3β (Ser9) levels to decrease GSK‐3β activation (Figure B). The GSK‐3β inhibitor LiCl effectively inhibited inflammatory cytokines by the increasing GSK‐3β (Ser9) phosphorylation and GSK‐3β inactivation . Compared to LiCl treatment, K313 better inhibited NO, IL‐6, and TNF‐α secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is produced from the conversion of arachidonic acid by the inducible cyclooxygenase isoform, COX-2, which is induced by cytokines and other activators 15 . Therefore, we next examined the effects of RFE on PGE 2 production in LPS-stimulated RAW 264.7 macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…It then upregulates the expression of cytokines, including McP-1, IL-6, TNF-α, and NO (47). Several studies have indicated that NF-κB may serve an important role in LPS-induced inflammation in macrophages and VSMcs (48,49). As a downstream molecule of TAK1, a reduction in NF-κB may contribute to the anti-inflammatory mechanism of Tan IIA.…”
Section: Discussionmentioning
confidence: 99%